Suppression of tumorigenicity with continued expression of the c-Ha-ras oncogene in EJ bladder carcinoma-human fibroblast hybrid cells. - Geiser, A G (1986)
A human tumor cell line (EJ) expressing an activated c-Ha-ras oncogene was fused with a normal human fibroblast cell line. This fusion resulted in hybrids that behaved as transformed cells in culture but failed to form tumors in nude (athymic) mice. After repeated cell passage, two tumorigenic segregants of the hybrids arose in culture. The levels of expression of activated c-Ha-ras mRNA and its protein product, p21, were similar in the EJ cell line, the nontumorigenic hybrids, and the tumorigenic segregants. DNA transfections of the hybrids were performed with activated c-Ha-ras plasmid constructs, and transfectants expressing a 2-fold level of c-Ha-ras relative to the hybrid cells were found to maintain the nontumorigenic phenotype. We suggest that expression of the active c-Ha-ras oncogene is insufficient for the malignant transformation of these human cells.